TEACHING THE VARIETY OF SYNTACTIC STRUCTURES USING ENGLISH LANGUAGE NEWSPAPER HEADLINES - Iļjina, Svetlana; Prikule, Valentīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The research examines the variety of syntactic structures that are used in formation of newspaper headlines in British press. The report focuses on the peculiarities of newspaper headlines in terms of their syntactic structure. The present study also points out the influence of the sentence structure on the meaning of the entire headline.